Histamine release factor encoding gene in Hyalomma anatolicum ticks is over-expressed during deltamethrin exposure - Mohammed H. Al-Saadi; Israa M. Essa; Akram M. Amanah; Ali M. Essa (Iraqi Journal of Veterinary Sciences)
Ticks have evolved complex strategies to parasitize their hosts successfully. They are considered vectors for various pathogens that can infect humans and animals. Moreover, using acaricide has increased dramatically all over the world. Nevertheless, ticks have developed resistance to numerous acaricides. Thus, demonstrating the effect of deltamethrin on a hard tick (Hyalomma anatolicum) to estimate the level of Histamine Release Factor (HRF) using an RT-qPCR assay is important for future experimental studies, such as resistance tick identification. Also, conventional PCR was performed to confirm the species of ticks. To do this, three pairs of primers were designed in this study to demonstrate the expression level of HRF while identifying the optimal conditions. The RT-qPCR assay revealed successful amplification of the targeted HRF gene to quantify its mRNA expression. Ticks from each group were exposed to deltamethrin for two hours and then analysed for HRF mRNA expression. Also, genomic DNA was extracted for tick identification. The results revealed a significant upregulation in the exposed group with a fold change value of 4.3± 0.5. At the same time, the level was lower in the control group at 1.69±0.4. Hyalomma anatolicum was found to be the predominant species in the studied region. This represents the first study in Iraq to target the effect of deltamethrin on the expression of HRF. Therefore, further studies are important to detect other tick genes that could contribute to their sensitivity or resistance to different types of acaricides and the following strategies for controlling ticks.